Influence of proteinoids on calcium carbonate polymorphs precipitation in supersaturated solutions - Panagiotis Mougkogiannis; Andrew Adamatzky (Results in Chemistry)
Proteinoids, or thermal proteins, are amino acid polymers formed at high temperatures by non-biological processes. Pro- teinoids form microspheres in liquids. The microspheres exhibit electrical activity similar to that of neurons. The electrically spiking microspheres are seen as proto-neurons capable of forming networks and carrying out information transmission and processing. Previously, we demonstrated that ensembles of proteinoid microspheres can respond to optical and electrical stimulation, implement logical gates, recognise arbitrary wave forms, and undergo learning. Thus, the ensembles of proteinoid microspheres can be seen as proto-brains. In present paper we decided to uncover morphologies of these proto-brains. We utilise a supersaturated solution of calcium carbonate to facilitate the crystallisation of proteinoids and subsequently generate proteinoid brain structures. Our hypothesis suggests that calcium carbonate crystals have the potential to serve as scaffolds and connectors for proteinoid microspheres, thereby improving their electrical properties and facilitating communication. In this section, we outline the experimental methods and techniques used in our study. We share our findings and results regarding the morphology, composition, stability, and functionality of proteinoid brain structures. We discuss the implications and applications of our work in the fields of bio-inspired computing, artificial neural networks, and origin of life research.